Low-intensity pulsed ultrasound stimulation in different regions in the viability of myocutaneous flaps. Issue 1 (December 2016) - Albuquerque, Fernanda; Neves, Lais; Guirro, Elaine
Abstract Background Low-intensity pulsed ultrasound (LIPUS) has presented good results in the healing of chronic wounds. The objective of this study was to compare the effect of LIPUS on the viability of transverse rectus abdominal muscle (TRAM) flap in different regions (central and epigastric) in rats. Methods Twenty-one Wistar male rats were homogeneously distributed into three groups as follows: group 1 (control), animals submitted to surgery only; group 2, animals submitted to surgery and application of LIPUS at the center of the flap; and group 3, animals submitted to surgery and application of LIPUS at the flap area corresponding to the right inferior epigastric artery pedicle. Stimulation was performed immediately after the surgery and within the following 2 days. The percentage of flap necrosis was evaluated by using the ImageJ® software as well as by measuring the temperature variation with infrared thermography (FLIR® T300). Results In the percentage calculation of the necrosis area, the application of LIPUS at the center of the flap (group 2) showed significantly smaller difference (26.2 %) compared to group 1 (54.50 %) and group 3 (44.01 %). Analysis of the temperature variation between the groups was performed by using the one-way ANOVA followed by Tukey's test. The results showed that both forms of LIPUS application showed significant differences compared to the control group. Conclusions In view of our results, one can conclude that the application of LIPUS at the center of the flap was effective for the viability of TRAM flap in reducing the necrosis area.